Method for testing content of silicon hydroxyl on surface of silica gel

By performing procedural heating and desorption and thermal conductivity detection in the protective gas atmosphere, the problem that the prior art cannot accurately determine the silicon hydroxyl content on the surface of the modified silicone is solved, and the accurate measurement of modified and unactivated silicone is achieved. Support silica gel for polyolefin activated at high temperature.

CN119470543APending Publication Date: 2025-02-18PETROCHINA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310998280.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing testing methods cannot accurately determine the silicon hydroxyl content on the surface of the modified silica gel, and are not suitable for carrier silica gel for polyolefins after high temperature activation.

Method used

In the protective gas atmosphere, the silicone sample is transferred to the quartz wool in a high-temperature resistant container, and the silicon hydroxyl group is desorbed through the program heating. The silicon hydroxyl group content on the silicone surface is calculated using the thermal conductivity detection signal and the standard curve of the water vapor content. .

Benefits of technology

Accurate determination of the hydroxyl content of the silicone on the surface of modified silica gel and unactivated silica gel is achieved, and is suitable for polyolefin carrier silica gel after high temperature activation, avoiding the problem of water and oxygen sensitivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004385470310000161
    Figure BDA0004385470310000161
  • Figure BDA0004385470310000171
    Figure BDA0004385470310000171
  • Figure BDA0004385470310000172
    Figure BDA0004385470310000172
Patent Text Reader

Abstract

The invention discloses two silica gel surface silicon hydroxyl content testing methods, which comprise: weighing and transferring / activating a silica gel sample, carrying out effective desorption on the silicon hydroxyl on the silica gel sample surface through temperature programming in a protective gas atmosphere with a larger air specific gravity, simultaneously detecting and recording a thermal conductivity detection signal, and combining with a standard curve to determine the content of the silicon hydroxyl on the silica gel surface. And the hydroxyl content on the surface of the silica gel sample can be accurately and truly calculated. The whole testing process is carried out in a water-free and oxygen-free environment, and the method is not only suitable for modified silica gel, but also suitable for non-activated silica gel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of analytical chemistry, and relates to a method for testing the content of silanol groups on the surface of silica gel. Background Art

[0002] Silica gel is a mineral material with light weight, porous, high dispersion, good chemical stability and thermal stability. It can be widely used in the fields of medicine and chemical industry, such as catalyst carrier, drug carrier, rubber reinforcing agent, optical fiber production, etc. Silica gel is the most widely studied and applied carrier at present, because it has high specific surface area, suitable pore volume and pore size distribution, good fluidity, suitable bulk density, suitable average particle size and particle size distribution, and suitable mechanical strength, etc., which can fully meet the needs of industrial production equipment.

[0003] As a polyolefin catalyst carrier material, silica gel is of great significance to the development of the polyolefin industry. At present, the catalyst carriers used in the existing Unipol process polyethylene production equipment and Phillips slurry loop process HDPE production equipment in my country are all silica gel, such as Unipol process polyethylene catalyst carrier, metallocene polyethylene catalyst carrier, Phillips process high-density polyethylene Cr series catalyst carrier and other single-active center catalyst carriers. The annual demand for catalyst silica gel carriers in China is about 500 tons. Although Chinese scientific researchers began to realize the localization of silica gel carriers for polyolefins in the 1980s, most of them are still imported.

[0004] Before the active metal is loaded, the polyolefin catalyst usually needs to be treated and modified differently on the surface of silica gel. Therefore, on the basis of requiring silica gel to have more mesoporous structure, higher bulk density and lower fine powder, another feature of silica gel is required - surface silanol group, which is the basis for silica gel to be chemically bonded or modified on the surface. The methods of modifying silica gel in the prior art are mainly divided into physical modification and chemical modification, among which physical modification is commonly used. The control of the number of silanol groups on the surface of silica gel is mainly achieved by activation and calcination under different conditions. The activation method includes programmed temperature (treatment temperature up to 600°C), different atmospheres (under N2 environment), and treatment of silica gel at different times to meet the requirements of silanol groups on the surface of different catalysts. At present, physical and chemical methods are mainly used to determine the silanol groups on the surface of silica gel, such as titration, isotope exchange, thermogravimetric analysis, nuclear magnetic analysis, infrared spectroscopy and other methods combined analysis.

[0005] For example, the journal document Mueller Roger, Hendrik K Kammler, et al. OH surface density of SiO2 and TiO2 by thermo-gracimetric analysis [J] Langmuir, 2003, 19 (1): 160-50 discloses the use of thermogravimetric analysis combined with LiAlH4 titration data for calibration to measure the surface hydroxyl content of the sample at 120-180°C. However, the modified silica gel cannot be exposed to air before loading, because the surface conditions of the silica gel are very complicated: the surface silanols can easily absorb water in the environment for hydrolysis, or be exposed to oxygen in the air for oxidation, resulting in inaccurate test results. This technology cannot solve the water-oxygen sensitivity problem of the modified silica gel, and is not suitable for carrier silica gel for polyolefins after high temperature (about 600°C) activation.

[0006] The journal Jean-Paul Gallas, Jean-Michel, et al. Quantification of water and silanol species on various silicas by coupling IR spectroscopy and in-situ thermogravimetry [J] Langmuir, 2009, 25 (10): 5828-5834. discloses that infrared spectroscopy and in-situ thermogravimetry are combined to achieve simultaneous infrared and thermogravimetric measurement, accurately determine the value of the molar comprehensive absorption coefficient, and then quantify the silanol content on the surface of the silica gel at 25°C according to the Beer-Lambert rule and the infrared absorption band corresponding to each substance. However, this solution also cannot solve the water-oxygen sensitivity problem of modified silica gel, and is not suitable for carrier silica gel for polyolefins after high temperature (about 600°C) activation.

[0007] In the paper “Application of Reaction Gas Chromatography to Determine Hydroxyl Groups in Silicone Analysis” published by Li Yufu et al. from the Institute of Chemistry, Chinese Academy of Sciences, precipitation method or gas phase method was used to dehydrate silica, which required ventilation outside the tube and heating to 120°C for half an hour. During the overall operation, the influence of isolated water and the effect of secondary hydration of the sample could not be avoided. Therefore, it is relatively difficult to test the hydroxyl content on the surface of silica gel for polyolefin carriers.

[0008] It can be seen that although infrared spectroscopy, thermogravimetry or their combination can determine the hydroxyl groups on the surface of silica gel, they are not suitable for the determination of silanol groups in silica gel for polyolefin carriers, because they cannot avoid the problem of water and oxygen sensitivity of the carrier after activation. Therefore, how to accurately determine the true silanol content in silica gel, especially the true hydroxyl content on the surface of silica gel after activation, is crucial to ensure the loading process of polyolefin catalysts and the activity of the catalyst. Summary of the invention

[0009] The purpose of the present invention is to provide two testing methods for the silanol content on the surface of silica gel, so as to solve the problems that the existing testing methods cannot accurately determine the silanol content on the surface of modified silica gel (the hydroxyl groups in the silica gel will be hydrated or oxidized when in contact with water and oxygen in the air), cannot truly determine the silanol content; and are not suitable for the determination of the silanol content in carrier silica gel for polyolefins after high temperature (about 600°C) activation.

[0010] To achieve the above object, the present invention provides the following technical solutions:

[0011] A method for testing the silanol content on the surface of silica gel comprises the following steps:

[0012] Transfer: In a protective gas atmosphere, transfer the accurately weighed modified silica gel sample to the quartz wool in a high temperature resistant container;

[0013] Desorption: The transferred modified silica gel sample is subjected to programmed temperature increase to desorb the silanol groups therein; and the thermal conductivity detection signal is recorded at the same time;

[0014] Quantitative analysis: Calculate the silanol content on the surface of the modified silica gel sample based on the recorded thermal conductivity detection signal and the calibration curve between the water vapor content and the thermal conductivity detection signal;

[0015] Wherein, the desorption step is carried out in a flowing protective gas atmosphere, and the protective gas is a gas with a specific gravity heavier than air.

[0016] The present invention also provides another method for testing the silanol content on the surface of silica gel, comprising the following steps:

[0017] Transfer: Transfer the accurately weighed unactivated silica gel sample onto the quartz wool in a high temperature resistant container;

[0018] Activation: The weighed unactivated silica gel sample is heated to desorb the adsorbed water on its surface, and then cooled to room temperature to obtain an activated silica gel sample;

[0019] Desorption: programming the temperature of the activated silica gel sample to desorb the silanol groups therein; and simultaneously recording the thermal conductivity detection signal;

[0020] Quantitative analysis: Calculate the silanol content on the surface of the unactivated silica gel sample based on the recorded thermal conductivity detection signal and the calibration curve between the water vapor content and the thermal conductivity detection signal;

[0021] Wherein, the desorption step and the activation step are both carried out in a flowing protective gas atmosphere, and the protective gas is a gas with a specific gravity heavier than air.

[0022] Optionally, in the desorption step of the two methods for testing the silanol content on the surface of silica gel provided by the present invention, the rate of the programmed temperature rise is 1 to 20°C / min, preferably 5 to 10°C / min;

[0023] The average particle sizes of the unactivated silica gel sample and the modified silica gel sample are both greater than 25 microns.

[0024] Optionally, in the desorption step of the above two test methods provided by the present invention, the rate of the programmed temperature increase is 5 to 10°C / min; the range of the programmed temperature increase is room temperature to 1200°C, preferably room temperature to 900°C;

[0025] The temperature was raised to the set temperature and maintained for 30-60 minutes, then naturally dropped to room temperature.

[0026] Optionally, in the desorption step of the two methods for testing the silanol content on the surface of silica gel provided by the present invention, the flow rate of the protective gas during the programmed temperature rise process is 5 to 50 mL / min, preferably 20 to 40 mL / min.

[0027] Optionally, in the desorption step of the above two methods for testing the silanol content on the surface of silica gel provided by the present invention, the programmed temperature is carried out in a dynamic programmed temperature rising instrument, and the dynamic programmed temperature rising instrument is provided with a thermal conductivity detector for detecting and recording signals; preferably, during the process of detecting and recording signals by the thermal conductivity detector, an online gas analyzer is turned on and the MID scanning mode is adopted to record the signal of 18 mass numbers.

[0028] Optionally, in the above two methods for testing the silanol content on the surface of silica gel provided by the present invention, the protective gas is Ar gas, Kr gas or Xe gas, preferably Ar gas;

[0029] The oxygen content in the protective gas is less than 0.01 ppm, and the water content is less than 0.01 ppm.

[0030] Optionally, in the activation step of the second method for testing the silanol content on the surface of silica gel provided by the present invention, the heating rate is 5 to 20°C / min, and the heating range is room temperature to 800°C;

[0031] After heating to the set temperature and maintaining it for 50-150 minutes, it naturally drops to room temperature;

[0032] The flow rate of the protective gas is 20-50 ml / min.

[0033] Optionally, in the transfer step of the above-mentioned first method for testing the silhydroxyl content on the surface of silica gel provided by the present invention, the accurately weighed modified silica gel sample is transferred to quartz wool in a high temperature resistant container in an atmosphere of protective gas in a glove box, and then the high temperature resistant container containing the modified silica gel sample is sealed and transferred out of the glove box; and the seal of the high temperature resistant container is opened in an atmosphere of flowing protective gas.

[0034] Optionally, in the transfer step of the above-mentioned first method for testing the silhydroxyl content on the surface of silica gel provided by the present invention, the flowing protective gas is placed on the seal of the high-temperature resistant container, and then the seal of the high-temperature resistant container is opened; preferably, the flow rate of the protective gas is 100 to 1000 mL / min, more preferably 100 to 200 ml / min.

[0035] Optionally, in the above-mentioned first test method for the silanol content on the surface of silica gel provided by the present invention (mainly for modified silica gel samples), in the transfer step, the outlet of the protective gas can be placed 2-3 mm above the seal of the high-temperature resistant container, while ensuring that the high-temperature resistant container containing the silica gel sample is in a flowing protective gas atmosphere to prevent the silica gel sample from contacting water and oxygen. At the same time, combined with quartz wool, the probability of loss caused by the silica gel sample being blown away can be further prevented.

[0036] Optionally, in the above two testing methods for the silanol content on the surface of silica gel provided by the present invention, the high temperature resistant container is not specifically limited, as long as it can withstand the high temperature in the desorption step, such as a quartz U-tube, a quartz beaker or a quartz glass tube, etc.

[0037] In the above two methods for testing the silanol content on the surface of silica gel provided by the present invention, the devices involved are not specifically limited and conventional devices in the industry that can meet the corresponding functional requirements can be used, such as a thermal conductivity detector in a dynamic program temperature rising instrument and a MID scanning mode in an online gas analyzer.

[0038] Optionally, in the above two testing methods for the silanol content on the surface of silica gel provided by the present invention, the mass range of the mass spectrometer MID scanning of the online gas analyzer is 1 to 300 amu, preferably 1 to 200 amu; the detection limit concentration is 5 ppb to 10 ppm, preferably 5 to 10 ppm.

[0039] Specifically, the first method for testing the silanol content on the surface of silica gel provided by the present invention is mainly for modified silica gel samples, and comprises the following steps:

[0040] Transfer: In the glove box, in the atmosphere of protective gas, transfer the accurately weighed modified silica gel sample to the quartz wool in the high temperature resistant container (quartz wool can prevent the silica gel sample from being blown away in the subsequent flowing protective gas atmosphere, resulting in inaccurate test results), and then seal the high temperature resistant container containing the modified silica gel sample and transfer it out of the glove box; turn on the protective gas and place it on the sealing part of the high temperature resistant container, and then open the sealing part of the high temperature resistant container to place the high temperature resistant container containing the modified silica gel sample in the flowing protective gas atmosphere;

[0041] Desorption: After replacing the air in the dynamic program temperature raising instrument with protective gas, the high temperature resistant container containing the modified silica gel sample in the flowing protective gas atmosphere is placed in the dynamic program temperature raising instrument, and the modified silica gel sample is subjected to program temperature raising to desorb the silanol groups in the modified silica gel sample; at the same time, the thermal conductivity detector in the dynamic program temperature raising instrument is used to detect and record the signal; at the same time, the online gas analyzer is turned on and the MID scanning mode is adopted to record the signal of 18 mass numbers;

[0042] Standard curve: Use shielding gas with different water vapor content as standard gas to establish a standard curve between shielding gas with different water vapor content and thermal conductivity detector signal;

[0043] Quantitative analysis: calculating the silanol content on the surface of the silica gel sample according to the detection signal of the thermal conductivity detector in the desorption step and the standard curve, combined with the mass of the modified silica gel;

[0044] The entire process of the desorption step and the calibration step is carried out in a flowing protective gas atmosphere, the protective gas is a gas heavier than air, and the protective gas is dehydrated and deoxygenated before use.

[0045] Specifically, the second method for testing the silanol content on the surface of silica gel provided by the present invention is mainly for unactivated silica gel samples and comprises the following steps:

[0046] Weighing: Transfer the accurately weighed unactivated silica gel sample to the quartz wool in the high temperature resistant container, then turn on the protective gas and place it at the opening of the high temperature resistant container, so that the high temperature resistant container containing the unactivated silica gel sample is in a flowing protective gas atmosphere;

[0047] Activation: After replacing the air in the dynamic program temperature raising instrument with protective gas, the high temperature resistant container containing the unactivated silica gel sample in the flowing protective gas atmosphere is placed in the dynamic program temperature raising instrument, and the unactivated silica gel sample is heated to desorb the adsorbed water on the surface of the unactivated silica gel sample; and then cooled to room temperature;

[0048] Desorption: the activated silica gel sample is subjected to a programmed temperature rise to desorb the silanol groups in the activated silica gel sample; at the same time, a thermal conductivity detector in the dynamic programmed temperature riser is used to detect and record the signal; and an online gas analyzer is turned on and the MID scanning mode is adopted to record the signal of 18 mass numbers;

[0049] Standard curve: Use shielding gas with different water vapor content as standard gas to establish a standard curve between shielding gas with different water vapor content and thermal conductivity detector signal;

[0050] Quantitative analysis: calculating the silanol content on the surface of the unactivated silica gel sample according to the detection signal of the thermal conductivity detector in the desorption step and the standard curve, combined with the mass of the unactivated silica gel sample;

[0051] The entire process of the desorption step and the calibration step is carried out in a flowing protective gas atmosphere, and the protective gas is a gas with a specific gravity heavier than air.

[0052] Compared with the prior art, the present invention has the following advantages:

[0053] The test method for the silanol content on the surface of silica gel provided by the present invention is not only applicable to modified silica gel, but also to unactivated silica gel. For modified silica gel, it is necessary to first weigh and transfer the modified silica gel sample in a protective gas atmosphere in a glove box; for unactivated silica gel, it is necessary to first activate the weighed unactivated silica gel to remove the physically adsorbed water and water of different temperature structures contained on the surface of the unactivated silica gel. Then, in a protective gas atmosphere with a specific gravity greater than that of air, the temperature is increased by adopting a heating program to effectively desorb the silanol on the surface of the modified silica gel / activated silica gel. During desorption, a thermal conductivity detector in a dynamic program temperature increasing instrument is used to detect and record the signal. Combined with the calibration curve, the hydroxyl content on the surface of the corresponding silica gel sample can be accurately and truly calculated; during desorption, the MID scanning mode of the online gas analyzer is used to measure and record the signal of 18 mass numbers for qualitative analysis; the whole process is carried out in an anhydrous and oxygen-free environment. Among them, the structures of the unactivated silica gel and the activated silica gel are respectively as shown in Figure 3 and Figure 4 As shown by Figure 3 and Figure 4 It can be seen that the physically adsorbed water and water with different temperature structures on the surface of unactivated silica gel can be removed by calcination under vacuum or protective gas conditions (such as calcination at 600-850°C), and then the silanol content can be determined to improve the measurement accuracy.

[0054] In addition, the detection method provided by the present invention is not only suitable for the accurate measurement of silanol on the surface of silica gel at room temperature, but also suitable for the determination of silanol content in silica gel carriers for polyolefins after high-temperature (about 850°C) activation, which provides a guarantee for optimizing the loading scheme of polyolefin silica gel carriers and active metals. With the transformation and upgrading of oil refining to high-end chemical materials, more high-quality high-end polyolefin catalysts will need to be developed in the future. The silanol content on the surface of silica gel is a key indicator. The detection method provided by the present invention provides a basic guarantee for ensuring the high-quality development of catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 A schematic diagram of the transfer of a silica gel sample provided by the present invention;

[0056] Figure 2 A schematic diagram of the process of establishing a standard curve provided by the present invention;

[0057] Figure 3 It is a schematic diagram of the structure of unactivated silica gel;

[0058] Figure 4 Schematic diagram of the structure of activated silica gel. DETAILED DESCRIPTION

[0059] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.

[0060] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0061] For the convenience of comparison, the following embodiments all use an online gas analyzer with a detection mass range of 1 to 300 amu and a detection limit concentration of 5 ppb to 10 ppm. In addition, the oxygen content and water content of the protective gas used in each embodiment are all less than 0.01 ppm and 0.01 ppm, respectively.

[0062] Example 1

[0063] This embodiment provides a method for testing the silanol content on the surface of modified silica gel, and the specific steps are as follows:

[0064] Transfer: As Figure 1As shown, in a glove box with an Ar atmosphere, quartz wool is placed at the bottom of one side of a U-shaped tube (quartz material), and then 0.5 g of a modified silica gel sample (with a particle size of 25-100 microns) is accurately weighed and placed on top of the quartz wool. Finally, both ends of the U-shaped tube are sealed with a sealing film and transferred out of the glove box; then the Ar gas is turned on and the flow rate is adjusted to 120 mL / min, and the upper part of the end of the U-shaped tube where the modified silica gel sample is not placed is placed 2-3 mm away from the port, and then the sealing films at both ends of the U-shaped tube are opened so that the U-shaped tube containing the modified silica gel sample is in a flowing Ar gas atmosphere;

[0065] Desorption: Turn on the dynamic program temperature riser and the Ar gas pipeline connected to it, adjust the Ar gas flow rate to 20ml / min, and purge the dynamic program temperature riser for 5min to replace the air in it, then put the U-tube containing the modified silica gel sample in the flowing Ar gas atmosphere into the dynamic program temperature riser, and then keep the Ar gas flow rate at 20ml / min, and heat the modified silica gel sample from room temperature to 1000℃ at a rate of 5℃ / min, and keep it at 1000℃ for 60min, and then naturally cool it to room temperature. During the entire process of heating and maintaining high temperature, the thermal conductivity detector in the dynamic program temperature riser detects and records the signal, and at the same time, the online gas analyzer is turned on and the MID scanning mode is used to record the signal of 18 mass numbers;

[0066] Song: As attached Figure 2As shown, two pipelines are connected in parallel at the outlet of the protective gas storage tank. The first pipeline is only provided with a mass flow controller MFC for adjusting the flow rate of the protective gas, and the second pipeline is provided with a mass flow controller MFC and a water-containing beaker for adjusting the flow rate of the protective gas in sequence. The water vapor rising from the water-containing beaker after heating is mixed with the protective gas measured by the MFC to form a mixed gas. The flow rates of the protective gas measured by the MFC on the first pipeline and the second pipeline are controlled to be the same. The protective gas measured by the MFC on the first pipeline enters the dynamic program temperature rising instrument and is detected by the thermal conductivity detector TCD and the signal N1 is recorded. The mixed gas formed by the protective gas and water vapor measured by the MFC on the second pipeline enters the dynamic program temperature rising instrument and is detected by the thermal conductivity detector TCD and the signal N2 is recorded. The signals of the whole program temperature rising and the high temperature are recorded, wherein N1 and N2 are stable signals after the high temperature is maintained. The water content in the mixed gas is adjusted by adjusting the flow rate, and a standard curve between the TCD signal value and the water content is established. The water content control method is based on 100ml / min as an example, the flow rate of the first pipeline is controlled at 100ml / min, and the flow rate of the second pipeline is 0, then the water vapor content of the gas entering the TCD is 0; if the flow rate of the first pipeline is controlled at 0ml / min, and the flow rate of the second pipeline is 100mL / min, then the saturated vapor pressure of water vapor is calculated as 31mPa, and the water content in 100mL / min gas is 3.16%; therefore, by controlling the total flow rate to remain unchanged at 100mL / min and adjusting the flow rate of the second pipeline, the proportion of water vapor in the gas passing through the TCD can be adjusted, thereby establishing a standard curve between the TCD signal value and water vapor.

[0067] The temperature program of the dynamic program temperature riser was the same as that of the desorption step (the modified silica gel sample was heated from room temperature to 600°C at a rate of 5°C / min and kept at 600°C for 50 min).

[0068] The mass content of water vapor in the mixed gas entering the dynamic programmed temperature apparatus in the second pipeline is controlled to be 0, 0.5%, 1%, 1.5% and 3.16% respectively. The water vapor content in the mixed gas is used as the horizontal coordinate, and the signal (N2-N1) recorded by the thermal conductivity detector TCD is used as the vertical coordinate. The standard curve constructed is the standard curve between the TCD signal and water vapor.

[0069] Quantification: The signal value recorded by the thermal conductivity detector in the desorption step was substituted into the above standard curve for calculation. The surface silanol content of the modified silica gel sample tested was 3.2 mmol / g.

[0070] Example 2

[0071] This embodiment provides a method for testing the silanol content on the surface of modified silica gel, and the specific steps are as follows:

[0072] Transfer: As Figure 1 As shown, in a glove box with a Kr gas atmosphere, quartz wool is placed at the bottom of one side of a U-shaped tube (quartz material), and then 0.25 g of a modified silica gel sample (with a particle size concentrated in the range of 60-80 microns) is accurately weighed and placed on top of the quartz wool. Finally, both ends of the U-shaped tube are sealed with a sealing film and transferred out of the glove box; then the Kr gas is turned on and the flow rate is adjusted to 100 mL / min, and the upper part of one end of the U-shaped tube where the modified silica gel sample is not placed is placed 2-3 mm away from the port, and then the sealing films at both ends of the U-shaped tube are opened so that the U-shaped tube containing the modified silica gel sample is in a flowing Kr gas atmosphere;

[0073] Desorption: Turn on the dynamic program temperature riser and the Kr gas pipeline connected to it, adjust the Kr gas flow rate to 30ml / min, and purge the dynamic program temperature riser for 30min to replace the air in it, then put the U-shaped tube containing the modified silica gel sample in the flowing Kr gas atmosphere into the dynamic program temperature riser, and then adjust the Kr gas flow rate to 15ml / min, and heat the modified silica gel sample from room temperature to 600℃ at a rate of 2℃ / min, and keep it at 600℃ for 30min, and then naturally cool it to room temperature. During the entire process of heating and maintaining high temperature, the thermal conductivity detector in the dynamic program temperature riser detects and records the signal, and at the same time, the online gas analyzer is turned on and the MID scanning mode is used to record the signal of 18 mass numbers;

[0074] Quantitative analysis: Based on the standard curve constructed in Example 1 and in combination with the signal recorded by the thermal conductivity detector in the desorption step of this example, the surface silanol content of the modified silica gel sample detected was calculated to be 4.5 mmol / g.

[0075] Example 3

[0076] This embodiment provides a method for testing the silanol content on the surface of modified silica gel, and the specific steps are as follows:

[0077] Transfer: As Figure 1 As shown, in a glove box with a Xe gas atmosphere, quartz wool is placed at the bottom of one side of a U-shaped tube (quartz material), and then 0.7 g of a modified silica gel sample (with a particle size concentrated in 40-60 microns) is accurately weighed and placed on top of the quartz wool, and finally both ends of the U-shaped tube are sealed with a sealing film and transferred out of the glove box; then Xe is turned on and the flow rate is adjusted to 150 mL / min, and the upper part of one end of the U-shaped tube where the modified silica gel sample is not placed is placed 2-3 mm away from the port, and then the sealing films at both ends of the U-shaped tube are opened so that the U-shaped tube containing the modified silica gel sample is in a flowing Xe gas atmosphere;

[0078] Desorption: Turn on the dynamic program temperature riser and the Ar gas pipeline connected to it, adjust the Ar gas flow rate to 40ml / min, and purge the dynamic program temperature riser for 20min to replace the air in it, then put the U-tube containing the modified silica gel sample in the flowing Ar gas atmosphere into the dynamic program temperature riser, and then adjust the Ar gas flow rate to 25ml / min, and heat the modified silica gel sample from room temperature to 600℃ at a rate of 3℃ / min, and keep it at 600℃ for 40min, and then naturally cool it to room temperature. During the entire process of heating and maintaining high temperature, the thermal conductivity detector in the dynamic program temperature riser detects and records the signal, and at the same time, the online gas analyzer is turned on and the MID scanning mode is used to record the signal of 18 mass numbers;

[0079] Quantitative analysis: Based on the standard curve constructed in Example 1 and in combination with the signal recorded by the thermal conductivity detector in the desorption step of this example, the surface silanol content of the modified silica gel sample detected was calculated to be 1.6 mmol / g.

[0080] Example 4

[0081] This embodiment provides a method for testing the silanol content on the surface of modified silica gel, and the specific steps are as follows:

[0082] Transfer: As Figure 1 As shown, in a glove box with an Ar atmosphere, quartz wool is placed at the bottom of one side of a U-shaped tube (quartz material), and then 0.05 g of a modified silica gel sample (with a particle size concentrated in the range of 30-50 microns) is accurately weighed and placed on top of the quartz wool. Finally, both ends of the U-shaped tube are sealed with a sealing film and transferred out of the glove box; then the Ar gas is turned on and the flow rate is adjusted to 120 mL / min, and the upper part of one end of the U-shaped tube where the modified silica gel sample is not placed is placed 2-3 mm away from the port, and then the sealing films at both ends of the U-shaped tube are opened so that the U-shaped tube containing the modified silica gel sample is in a flowing Ar gas atmosphere;

[0083] Desorption: Turn on the dynamic program temperature riser and the Xe gas pipeline connected to it, adjust the Xe gas flow rate to 50ml / min, and purge the dynamic program temperature riser for 10min to replace the air in it, then put the U-tube containing the modified silica gel sample in the flowing Xe gas atmosphere into the dynamic program temperature riser, and then adjust the Xe gas flow rate to 30ml / min, and heat the modified silica gel sample from room temperature to 600℃ at a rate of 10℃ / min, and keep it at 600℃ for 50min, and then naturally cool it to room temperature. During the entire process of heating and maintaining high temperature, the thermal conductivity detector in the dynamic program temperature riser detects and records the signal, and at the same time, the online gas analyzer is turned on and the MID scanning mode is used to record the signal of 18 mass numbers;

[0084] Quantitative analysis: Based on the standard curve constructed in Example 1 and in combination with the signal recorded by the thermal conductivity detector in the desorption step of this example, the surface silanol content of the modified silica gel sample detected was calculated to be 5.2 mmol / g.

[0085] Example 5

[0086] This embodiment provides a method for testing the silanol content on the surface of unactivated silica gel, and the specific steps are as follows:

[0087] Weighing: In an air atmosphere, put quartz wool at the bottom of one side of a U-shaped tube (quartz material), then accurately weigh 0.05g of unactivated silica gel sample (particle size concentrated in 70-120 microns) and put it on top of the quartz wool, then turn on the Xe gas and adjust the flow rate to 120mL / min, and place the upper part of one end of the U-shaped tube containing the unactivated silica gel sample 2-3mm away from the port, so that the U-shaped tube containing the unactivated silica gel sample is in a flowing Xe gas atmosphere;

[0088] Activation: Turn on the dynamic programmed temperature rising instrument and the Ar gas pipeline connected to it, adjust the Ar gas flow rate to 50 ml / min, and purge the dynamic programmed temperature rising instrument for 10 minutes to replace the air in it, then place the U-tube containing the unactivated silica gel sample in the flowing Ar gas atmosphere into the dynamic programmed temperature rising instrument, and then adjust the Ar gas flow rate to 50 ml / min, first raise the temperature of the modified silica gel sample from room temperature to 650°C at a rate of 10°C / min, and keep it at 650°C for 100 minutes, and then naturally cool it to room temperature.

[0089] Desorption: Keep the Ar gas flow rate at 50 ml / min, purge the dynamic program temperature riser for 45 min, and then heat the activated silica gel sample from room temperature to 900 °C at a rate of 10 °C / min. During the whole process of heating and maintaining high temperature, the thermal conductivity detector in the dynamic program temperature riser detects and records the signal, and at the same time, the online gas analyzer is turned on and the MID scanning mode is adopted to record the signal of 18 mass numbers.

[0090] Quantitative analysis: Based on the standard curve constructed in Example 1 and in combination with the signal recorded by the thermal conductivity detector in the desorption step of this example, the surface silanol content of the detected unactivated silica gel sample was calculated to be 6.1 mmol / g.

[0091] Example 6

[0092] This embodiment provides a method for testing the silanol content on the surface of modified silica gel, and the specific steps are as follows:

[0093] Transfer: As Figure 1As shown, in a glove box with a Kr gas atmosphere, quartz wool is placed at the bottom of one side of a U-shaped tube (quartz material), and then 0.4 g of a modified silica gel sample (with a particle size concentrated in the range of 80-120 microns) is accurately weighed and placed on top of the quartz wool, and finally both ends of the U-shaped tube are sealed with a sealing film and transferred out of the glove box; then the Kr gas is turned on and the flow rate is adjusted to 1000 mL / min, and the upper part of one end of the U-shaped tube where the modified silica gel sample is not placed is placed 2-3 mm away from the port, and then the sealing films at both ends of the U-shaped tube are opened so that the U-shaped tube containing the modified silica gel sample is in a flowing Kr gas atmosphere;

[0094] Desorption: Turn on the dynamic program temperature riser and the Ar gas pipeline connected to it, adjust the Ar gas flow rate to 20ml / min, and purge the dynamic program temperature riser for 10min to replace the air in it, then put the U-shaped tube containing the modified silica gel sample in the flowing Ar gas atmosphere into the dynamic program temperature riser, and then adjust the Ar gas flow rate to 20ml / min, and heat the modified silica gel sample from room temperature to 900℃ at a rate of 2℃ / min, and keep it at 900℃ for 60min, and then naturally cool it to room temperature. During the entire process of heating and maintaining high temperature, the thermal conductivity detector in the dynamic program temperature riser detects and records the signal, and at the same time, the online gas analyzer is turned on and the MID scanning mode is used to record the signal of 18 mass numbers;

[0095] Quantitative analysis: Based on the standard curve constructed in Example 1 and in combination with the signal recorded by the thermal conductivity detector in the desorption step of this example, the surface silanol content of the modified silica gel sample tested was calculated to be 4.5 mmol / g.

[0096] Example 7

[0097] This embodiment provides a method for testing the silanol content on the surface of modified silica gel, and the specific steps are as follows:

[0098] Transfer: As Figure 1 As shown, in a glove box with a Kr gas atmosphere, quartz wool is placed at the bottom of one side of a U-shaped tube (quartz material), and then 0.25 g of a modified silica gel sample (with a particle size concentrated in the range of 20-50 microns) is accurately weighed and placed on top of the quartz wool. Finally, both ends of the U-shaped tube are sealed with a sealing film and transferred out of the glove box; then the Kr gas is turned on and the flow rate is adjusted to 500 mL / min, and the upper part of one end of the U-shaped tube where the modified silica gel sample is not placed is placed 2-3 mm away from the port, and then the sealing films at both ends of the U-shaped tube are opened so that the U-shaped tube containing the modified silica gel sample is in a flowing Kr gas atmosphere;

[0099] Desorption: Turn on the dynamic program temperature riser and the Ar gas pipeline connected to it, adjust the Ar gas flow rate to 5 ml / min, and purge the dynamic program temperature riser for 20 minutes to replace the air in it, then put the U-shaped tube containing the modified silica gel sample in the flowing Ar gas atmosphere into the dynamic program temperature riser, and then adjust the Ar gas flow rate to 5 ml / min, and heat the modified silica gel sample from room temperature to 950°C at a rate of 20°C / min, and keep it at 950°C for 60 minutes, and then naturally cool it to room temperature. During the entire process of heating and maintaining high temperature, the thermal conductivity detector in the dynamic program temperature riser detects and records the signal, and at the same time, the online gas analyzer is turned on and the MID scanning mode is used to record the signal of 18 mass numbers;

[0100] Quantitative analysis: Based on the standard curve constructed in Example 1 and in combination with the signal recorded by the thermal conductivity detector in the desorption step of this example, the surface silanol content of the modified silica gel sample detected was calculated to be 5.7 mmol / g.

[0101] Example 8

[0102] This embodiment provides a method for testing the silanol content on the surface of modified silica gel, and the specific steps are as follows:

[0103] Transfer: As Figure 1 As shown, in a glove box with a Kr gas atmosphere, quartz wool is placed at the bottom of one side of a U-shaped tube (quartz material), and then 1.0 g of a modified silica gel sample (with a particle size concentrated in the range of 50-120 microns) is accurately weighed and placed on top of the quartz wool. Finally, both ends of the U-shaped tube are sealed with a sealing film and transferred out of the glove box; then the Kr gas is turned on and the flow rate is adjusted to 600 mL / min, and the upper part of one end of the U-shaped tube where the modified silica gel sample is not placed is placed 2-3 mm away from the port, and then the sealing films at both ends of the U-shaped tube are opened so that the U-shaped tube containing the modified silica gel sample is in a flowing Kr gas atmosphere;

[0104] Desorption: Turn on the dynamic program temperature riser and the Ar gas pipeline connected to it, adjust the Ar gas flow rate to 5 ml / min, and purge the dynamic program temperature riser for 30 minutes to replace the air in it, then put the U-shaped tube containing the modified silica gel sample in the flowing Ar gas atmosphere into the dynamic program temperature riser, and then adjust the Ar gas flow rate to 5 ml / min, and heat the modified silica gel sample from room temperature to 900°C at a rate of 10°C / min, and keep it at 900°C for 30 minutes, and then naturally cool it to room temperature. During the entire process of heating and maintaining high temperature, the thermal conductivity detector in the dynamic program temperature riser detects and records the signal, and at the same time, the online gas analyzer is turned on and the MID scanning mode is used to record the signal of 18 mass numbers;

[0105] Quantitative analysis: Based on the standard curve constructed in Example 1 and in combination with the signal recorded by the thermal conductivity detector in the desorption step of this example, the surface silanol content of the modified silica gel sample detected was calculated to be 7.1 mmol / g.

[0106] Example 9

[0107] This embodiment provides a method for testing the silanol content on the surface of unactivated silica gel, and the specific steps are as follows:

[0108] Weighing: In an air atmosphere, put quartz wool at the bottom of one side of a U-shaped tube (quartz material), then accurately weigh 0.35g of unactivated silica gel sample (particle size concentrated in 80-150 microns) and put it on top of the quartz wool, then turn on the Ar gas and adjust the flow rate to 500mL / min, and place the upper part of one end of the U-shaped tube containing the unactivated silica gel sample 2-3mm away from the port, so that the U-shaped tube containing the unactivated silica gel sample is in a flowing Ar gas atmosphere;

[0109] Activation: Turn on the dynamic programmed temperature rising instrument and the Ar gas pipeline connected to it, adjust the Ar gas flow rate to 25 ml / min, and purge the dynamic programmed temperature rising instrument for 15 minutes to replace the air in it, then put the U-tube containing the unactivated silica gel sample in the flowing Ar gas atmosphere into the dynamic programmed temperature rising instrument, and then adjust the Ar gas flow rate to 30 ml / min, first increase the temperature of the modified silica gel sample from room temperature to 750°C at a rate of 15°C / min, and keep it at 750°C for 150 minutes, and then naturally cool it to room temperature.

[0110] Desorption: Keep the Ar gas flow rate at 35 ml / min, purge the dynamic program temperature riser for 50 min, and then heat the activated silica gel sample from room temperature to 900 °C at a rate of 10 °C / min. During the whole process of heating and maintaining high temperature, the thermal conductivity detector in the dynamic program temperature riser detects and records the signal, and at the same time, the online gas analyzer is turned on and the MID scanning mode is adopted to record the signal of 18 mass numbers.

[0111] Quantitative analysis: Based on the standard curve constructed in Example 1 and in combination with the signal recorded by the thermal conductivity detector in the desorption step of this example, the surface silanol content of the detected unactivated silica gel sample was calculated to be 3.7 mmol / g.

[0112] Experimental Example 1

[0113] The same sample in Example 1 / Example 9 was used respectively, and the same analyst repeated the test 9 times on the same device according to the test method in Example 1 / Example 9; the specific results are shown in Table 1.

[0114] The same sample in Example 1 / Example 9 was used respectively, and the test was performed by four analysts on four devices according to the test method in Example 1 / Example 9; the specific results are shown in Table 2.

[0115] Table 1 Repeatability test results

[0116]

[0117]

[0118] Table 2 Reproducibility test results

[0119]

[0120] It can be seen from the data in the above table that the test method for the silanol content on the surface of silica gel provided by the present invention can accurately determine the content of silanol on the surface of unactivated silica gel and modified silica gel as a carrier for polyolefins through method repeatability and reproducibility investigation, and can effectively avoid the influence of rehydration during silica gel activation on the test results.

[0121] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.

Claims

1. A method for testing the silanol content on the surface of silica gel, characterized in that: The steps include: Transfer: In a protective gas atmosphere, transfer the accurately weighed modified silica gel sample to the quartz wool in a high temperature resistant container; Desorption: The transferred modified silica gel sample is subjected to programmed temperature increase to desorb the silanol groups therein; and the thermal conductivity detection signal is recorded at the same time; Quantitative analysis: Calculate the silanol content on the surface of the modified silica gel sample based on the recorded thermal conductivity detection signal and the calibration curve between the water vapor content and the thermal conductivity detection signal; Wherein, the desorption step is carried out in a flowing protective gas atmosphere, and the protective gas is a gas with a specific gravity heavier than air.

2. A method for testing the silanol content on the surface of silica gel, characterized in that: The steps include: Transfer: Transfer the accurately weighed unactivated silica gel sample onto the quartz wool in a high temperature resistant container; Activation: The weighed unactivated silica gel sample is heated to desorb the adsorbed water on its surface, and then cooled to room temperature to obtain an activated silica gel sample; Desorption: programming the temperature of the activated silica gel sample to desorb the silanol groups therein; and simultaneously recording the thermal conductivity detection signal; Quantitative analysis: Calculate the silanol content on the surface of the unactivated silica gel sample based on the recorded thermal conductivity detection signal and the calibration curve between the water vapor content and the thermal conductivity detection signal; Wherein, the desorption step and the activation step are both carried out in a flowing protective gas atmosphere, and the protective gas is a gas with a specific gravity heavier than air.

3. The testing method according to claim 1 or 2, characterized in that: In the desorption step, the rate of the programmed temperature rise is 1 to 20°C / min; The average particle sizes of the unactivated silica gel sample and the modified silica gel sample are both greater than 25 microns.

4. The testing method according to claim 3, characterized in that: In the desorption step, the rate of the programmed temperature increase is 5 to 10°C / min; the range of the programmed temperature increase is room temperature to 1200°C; In the desorption step, the temperature is programmed to rise to a set temperature and maintained for 30-60 minutes, and then naturally dropped to room temperature.

5. The testing method according to claim 1 or 2, characterized in that: In the desorption step, the flow rate of the protective gas during the programmed temperature rise is 5 to 50 mL / min, preferably 20 to 40 mL / min.

6. The testing method according to claim 1 or 2, characterized in that: In the desorption step, the programmed temperature is carried out in a dynamic programmed temperature rising instrument, and the dynamic programmed temperature rising instrument is provided with a thermal conductivity detector for detecting and recording signals; preferably, during the process of detecting and recording signals by the thermal conductivity detector, an online gas analyzer is turned on and a MID scanning mode is adopted to record a signal of 18 mass numbers.

7. The testing method according to claim 1 or 2, characterized in that: The protective gas is Ar gas, Kr gas or Xe gas, preferably Ar gas; and / or The oxygen content in the protective gas is less than 0.01 ppm, and the water content is less than 0.01 ppm.

8. The testing method according to claim 2, characterized in that: In the activation step, the heating rate is 5 to 20°C / min, and the heating range is room temperature to 800°C; and / or In the activation step, the temperature is heated to a set temperature and maintained for 50-150 minutes, and then naturally cooled to room temperature; and / or In the activation step, the flow rate of the protective gas is 20-50 ml / min.

9. The testing method according to claim 1, characterized in that: In the transfer step, in a glove box in an atmosphere of protective gas, the accurately weighed modified silica gel sample is transferred to quartz wool in a high temperature resistant container, and then the high temperature resistant container containing the modified silica gel sample is sealed and transferred out of the glove box; and in an atmosphere of flowing protective gas, the seal of the high temperature resistant container is opened.

10. The testing method according to claim 9, characterized in that: In the transfer step, the flowing protective gas is placed on the seal of the high temperature resistant container, and then the seal of the high temperature resistant container is opened; preferably, the flow rate of the protective gas is 100 to 1000 mL / min, more preferably 100 to 200 ml / min.

Citation Information

Patent Citations

  • Determination method for hydroxyl value of terminal hydroxyl organic silicon molecule

    CN104391073A

  • Method for quantifying trace silicon hydroxyl in silicone oil

    CN112505203A

  • Method for determining silicon hydroxyl of white carbon black

    CN115127955A

  • Method for testing content of toluene in metallocene catalyst

    CN118837426A

  • Porous silica microspheres having silanol-enriched and silanized surfaces

    EP0221780A2